Navigating the New Normal in Industrial Countries. (per Jacobson lecture, 2010)
This paper discusses about the fact that longer the recognition problems persist, the greater the risk of continued 'active inertia' and disappointing outcomes. The possibility of policy mistakes and business accidents will increase further, it will become harder for industrial country governments to convince their citizenry (as well as decision makers in emerging economies) to participate fully in the formulation and implementation of the required solutions, and multilateral institutions will not be able to fill the growing void at the core of the international system. The innovative financial instruments were potent in lowering barriers to entry to many markets, including important segments of the US housing market. As a result, too many households purchased homes that they could not afford, using exotic mortgages they did not fully understand, and too many small companies took on debt they could not sustain. Prior to the crisis, key industrial countries had embarked upon a multiyear, serial contamination of balance sheets.